Between policy and perception: Stakeholder views on addressing territorial inequality in Europe [version 2; peer review: 1 approved, 2 approved with reservations] - Zarko Sunderic; Olga Jubany; Malin Roiha; Gordana Matkovic (Open Research Europe)
Background Long-standing territorial disparities have evolved into novel forms of inequality, exacerbated by a decline in social status and the protection afforded to citizens. Territorial inequality extends beyond economic disparities in income and wealth, encompassing unequal access to fundamental rights and opportunities such as essential services, infrastructure, and education. These disparities pose significant challenges to comprehensive socioeconomic development. This paper is part of a broader research project on “left-behindness,” aiming to explore stakeholders' perceptions of the underlying drivers of territorial inequalities, as well as the governance mechanisms and policy tools aimed at mitigating these issues. Methods The analysis draws on data from 20 focus groups conducted between November and December 2023, involving 98 national, regional and local stakeholders from seven European countries: Austria, Belgium, Denmark, Greece, Italy, Serbia, and Spain. Results The findings reveal a notable disconnect between national-level discourses on territorial inequalities and the priorities of local and regional stakeholders across the seven countries. While territorial disparities are acknowledged within policy frameworks, efforts to address these issues are often impeded by governance challenges, including tensions between centralization and decentralization, fragmented coordination, and insufficient horizontal and vertical cooperation among actors at different levels of government. Conclusions The research underscores the necessity of adopting place-sensitive, context-specific approaches to address territorial inequalities. It highlights the need to address demographic challenges, geographic isolation, and inequitable funding mechanisms, particularly in underserved regions. Aligning policy interventions with the diverse and context-dependent challenges faced by “left-behind” areas is essential for the effective mitigation of territorial disparities.